2012
DOI: 10.1128/aac.05919-11
|View full text |Cite
|
Sign up to set email alerts
|

Ajoene, a Sulfur-Rich Molecule from Garlic, Inhibits Genes Controlled by Quorum Sensing

Abstract: ABSTRACTIn relation to emerging multiresistant bacteria, development of antimicrobials and new treatment strategies of infections should be expected to become a high-priority research area. Quorum sensing (QS), a communication system used by pathogenic bacteria likePseudomonas aeruginosato synchronize the expression of specific genes involved in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
244
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 382 publications
(264 citation statements)
references
References 77 publications
5
244
0
7
Order By: Relevance
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…Extracts of fruits (e.g., blackberries, cranberries, vanilla, and citrus) and herbs (e.g., rosemary and turmeric) and extracts and oils of other plant materials (garlic, clove, and cinnamon) and medicinal plants (e.g., betel nut and notoginsing) have all displayed QSI activity to some degree, typically found via inhibition of violacein production in the C. violaceum bioassay (137,138,(264)(265)(266)(267)(268)(269)(270)(271)(272)(273)(274)(275). In very few cases, however, have individual compounds been isolated or identified from these kinds of complex sources.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…From horseradish, the isothiocyanate iberin (Table 3) was identified and shown by transcriptome profiling to substantially inhibit expression of LasR-and RhlR-regulated genes in P. aeruginosa (137). From garlic extracts, an allyl sulfide called ajoene (Table 3) was isolated using the activity monitored by the QSIS reporter system (138,139). Interestingly, ajoene specifically affected a narrow set of QS-regulated genes in P. aeruginosa, including those involved in rhamnolipid production, and thus prevented P. aeruginosa biofilms from killing polymorphonuclear leukocytes in flow chambers, an effect attributable to rhamnolipid production (138,139).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that ajoene 2 is an effective QS inhibitor against Pseudomonas aeruginosa and Staphylococcus aureus and could be utilized for the treatment of chronic biofilm infections by exploiting the QS system 13. In this study, we employed a reporter strain ( Pseudomonas aeruginosa Pa01 lasB‐gfp )13a whereby QS gene expression was monitored over time in response to ajoene treatment.…”
mentioning
confidence: 99%